Sensitivity and specificity of bloody diarrhea in shigella gastroenteritis - Ozmert, Elif N; Orün, Emel; Sengelen, Meltem; Yalçin, S Songül; Yurdakök, Kadriye; Gür, Deniz (The Turkish Journal of Pediatrics, 2010)
The sensitivity and specificity of bloody diarrhea in the diagnosis of shigella gastroenteritis in a Shigella sonnei prevalent center was investigated. The shigella-proven gastroenteritis cases who were admitted to Hacettepe University Ihsan Doğramaci Children’s Hospital Diarrheal Diseases Unit (Jan 2003 - Oct 2006) constituted the study group (n=65). Age- and sex-matched children admitting to the same center with non-shigella diarrhea constituted the control group (n=65). The sensitivity, specificity, and positive and negative predictive values of bloody diarrhea were found to be 30%, 100%, 100% and 58%, respectively. Sensitivity of bloody diarrhea in the diagnosis of shigella gastroenteritis was low in this center. New strategies and recommendations in the management of mild nonbloody cases are needed.